Quick count training for junior high school teachers in Gayo Lues District - Priyanda, Roni; Amalia, Rizki; Zaki, Muhammad; Fadilah, Fadilah; Fadhelina, Nishbah; Ihsan, Iden Rainal (Community Empowerment, 2021)
This community service is carried out together with the Gayo Lues District Education Office. The purpose of this activity is to improve the speed counting skills and junior high school teachers in Gayo Lues, so that each teacher can become an agent of change in improving students' fast counting skills. The implementation of the activity began with a pre-test, discussion of partner problems, mentoring and training, review and evaluation by giving rewards to participants who get the best score. The results of the initial pre-test showed that the math teachers' ability to count quickly in Gayo Lues district was still low, where only 22.5% of the teachers were able to solve the questions according to the time given. However, after training and mentoring, more teachers were able to solve quick arithmetic questions according to the set time (75%). Although the level of accuracy is still low.